Formulation and Antibacterial Activity Test Staphylococcus Epidermidis as Microemulsion Preparation of Cherry Leaf Extract (Muntingia Calabura L.) Using the Oil Phase Isopropyl Myristate (IPM) - Rizky, Shinta Aprilia; Bhagawan, Weka Sidha; Annisa, Rahmi (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.361, 2017)
Cherry leaf ( Muntingia calabura L.) is one of the potential plants in the field of treatment, one of them as antibacterial in the treatment of anti-acne. Cherry leaf contains flavonoid compounds, saponins and tannins. This research is about the formulation of microemulsion of cherry leaf extract in improving penetration drug capability into skin.The purpose of this research is to know microemulsion chemistry and physic characteristics of cherry leaf extract and to know which one is the good formula based on microbial activity test of cherry leaf extract to Staphylococcus epidermidis . The results of this study showed that the microemulsion of cherry leaf extract had good characteristics on F2 with the concentration of 10% cherry leaf extract with clear brownish yellow color, peculiar leaf of cherry leaf, had pH value 5,94, type of microemulsion was oil in water (o/w) with the particle size was 15.01 nm, had an index polydispersity value of 0.22 <0.5, and can inhibit the growth of Staphylococcus epidermidis with antibacterial activity result was 8.34 ± 0.13. The microbial activity can be categorized as intermediate. Antibacterial activity using cendo xitrol as a positive control has an activity of 16.9 ± 0.51 with strong category.